Search for admixture of scalar top quarks in the t(t)over-bar lepton + jets final state at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Christofek, L.; et al. (Elsevier B.V., 2009)
A search for pair production of the lightest supersymmetric partner of the top quark, (t) over tilde (1), is performed in the lepton + jets channel using 0.9 fb(-1) of data collected by the D circle divide experiment. Kinematic differences between (t) over tilde (1)(t) over tilde (1) and the dominant top quark pair production background are used to separate the two processes. First limits from Run II of the Fermilab Tevatron Collider for the scalar top quark decaying to a chargino and a b quark ((t) over tilde1 -> (chi) over tilde (+)(1)b) are obtained for scalar top quark masses of 130-190 GeV and chargino masses of 90-150 GeV. (C) 2009 Elsevier B.V. All rights reserved.